G495(P) Child sexual abuse assessments: how well do we assess mental health risk and capture adverse childhood experiences?. (25th October 2020) - Stephenson, RL; Teebay, L; Willets, L
Abstract : Aims: To demonstrate identification and response to mental health issues in CYP (children and young people) who attend for sexual abuse assessments. To assess if information on ACEs (Adverse childhood experience) in this vulnerable population is collated. The outcome of the study will inform discussion regarding the clinician's role in addressing mental health and resilience factors for CYP. Methods: A retrospective review of 44 patient notes of cases seen January and June 2019 at the paediatric SARC (Sexual assault referral centre) based in an NHS setting. Data was collected on patient demographics, mental health issues, actions made and documentation of ACEs/resilience factors. Results: The majority, 93% n 41/44 of cases were female. Only 4 (9%) children had a documented mental health risk assessment. 22 (50%) were currently or previously known to social care prior to the assault and of these 22, 9 (40%) had mental health issues prior to the assault. Conclusion: A significant proportion of children and young people who access our SARC experience mental health issues and have a background of additional vulnerability and trauma. There is referral for specialist psychological assessment through the in house paediatric SARC clinical psychology service. Paediatricians identify mental health issues and risk, but this could be improved with training and standardised guidance. ACEs are prevalent in the caseload though figures are likely an under-representation because currently this information is assessed informally and is clinician-dependant. The CSA assessment is an opportunity to talk to CYP and families about mental health, ACEs and trauma with appropriate signposting. It is also an opportunity to work on building resilience in collaboration with a dedicated psychologist, social care, police, school and health visitors. Proposals: Focused mental health risk questions incorporated into the CSA proforma guiding onward intervention Develop a patient–led tool assisted by CYP user groups for collecting a robust ACE enquiry A bespoke 'Resilience plan' for each child. ACE –special interest group for sharing information and collaborating with other teams and multi–agencies.